Analisa Ketimpangan Pembangunan Ekonomi Pada Setiap Sektor Kecamatan Di Kabupaten Cilacap Tahun 2013-2018 - Sendy Zul Friandi; Adinda Heryuningtyas; Anggi Rechandini (UNIVERSITAS RAHARJA, 2019)
The research aims to: 1) Be able to know about the development of economic development in each sub-sector starting from 2013 to 2018. 2) Can know the role of the component influence on regional share growth towards the imbalance of economic development in each sub-sector of the district 3) Can know the role of the component influence on proportional shift growth towards the imbalance of economic development in each sector of the sub-district. 4) Can know the role of component influence on the competitive shift growth in economic development imbalances in each sector of the sub-district. 5) Can know the role of the influence of the number of population with the level of education of High School and Higher Education towards the imbalance of economic development in each sector of the sub-district. 6) Can know the effect of the total number of poor families on the imbalance of economic development in each sector of the sub-district. 7) Can know the effect of migration population growth on the imbalance of economic development in each sector of the sub-district.This research is also a descriptive and quantitative study. The data used in this study were secondary data types from 24 sub-districts in Cilacap Kabupaten taken in 2013-2018. The analysis technique that I use for the descriptive analysis method is using the Klassen Tipology matrix, while the quantitative analysis technique that I use to process panel data regression analysis is the Fixed Effect model.The results of this study can show that: 1) Based on Klassen's Tipology, not all sub-districts can experience positive development of economic development, because there are ten sub-districts that have declined to become negative fluctuating regions and have declined to relatively lagging regions. 2) Analysis using panel data regression can show regional share growth component variables that are not included or omitted from a model. 3) Component variable proportional shift growth does not only significantly influence the imbalance of economic development in the sub-district sector. 4) Variable components of competitive shift growth are seen to have a significant and positive effect on the inequality of economic development in the sub-district sector. 5) Variable number of population with the level of education of senior secondary and tertiary education has a significant and positive effect on the imbalance of economic development in the sub-district sector. 6) Variables of the number of poor families can have a significant and negative effect on the imbalance of economic development in the sub-district sector. 7) Variable migration population growth does not significantly influence the imbalance of economic development in the sub-district sector.